Development of Public Transport Shelter Integrated with Samsat Drive Thru Sidoarjo - Soni Wahyudi; Adhi Muhtadi (NAROTAMA UNIVERSITY, Indonesia, 2022)
The Sidoarjo Transportation Licensing Service Unit (UPPA) office building is located on Jalan Raya Pagerwaja, Ds Gelam, Kec. Temple, Kab. Sidoarjo, East Java, has been used by the local district government as a Samsat Drive Thru since 2021, where people can pay vehicle taxes from motorbikes or cars. Dishub will also develop a public transport shelter. especially those through the UPPA Building such as Angkot / MPU, Inter-City In- Province Transport (AKDP), and the planned Bus Rapid Transit which will operate in 2022. The method of calculating shelter needs used in this preparation uses the Single Channel - Single Phase & Multi Channel - Single Phase formula so that the final result of this study is the number of needs for each vehicle that carries out activities in the area. From the calculations that have been obtained from this study, the results obtained for vehicles; 1. The motorbike shows that the service level is optimal where there is one facility and one service stage using the Single Channel – Single Phase formula, 2. The car shows that the service level is optimal where there is one facility and one service stage using the Single Chanel formula – Single Phase, 3. City In-Province Transportation (AKDP) & Angkot / MPU based on calculations and data analysis showing shelter needs, namely 3 channels using the Multi Chanel - Single Phase formula, 4. Bus Rapid Transit (BRT) MPU based on calculations and data analysis shows the need for shelter, namely 2 channels using the Multi Channel - Single Phase formula.